Reciprocality Between Estrogen Biology and Calcium Signaling in the Cardiovascular System - Tran, Quang-Kim (Frontiers in Endocrinology, 2020)
17-estradiol (E2) is the main estrogenic hormone in the body and exerts many cardiovascular protective effects. Via three receptors known to date, including estrogen receptors α (ER),  (ER) and the G protein-coupled estrogen receptor 1 (GPER, a.k.a. GPR30), E2 regulates numerous calcium-dependent activities in cardiovascular tissues. Nevertheless, effects of E2 and its receptors on components of the calcium signaling machinery (CSM), the underlying mechanisms, and the linked functional impact are only beginning to be elucidated. A picture is emerging of reciprocality between estrogen biology and Ca2+ signaling. Therein, E2 and GPER, via both E2-dependent and -independent actions, moderate Ca2+-dependent activities; in turn, ERα and GPER are regulated by Ca2+ at the receptor level and downstream signaling via a feedforward loop. This article reviews current understanding of the effects E2 and its receptors on the cardiovascular CSM and vice versa with a focus on mechanisms and combined functional impact. An overview of the main CSM components in cardiovascular tissues will be first provided, followed by a brief review of estrogen receptors and their Ca2+-dependent regulation. The effects of estrogenic agonists to stimulate acute Ca2+ signals will then be reviewed. Subsequently, E2-dependent and -independent effects of GPER on components of the Ca2+ signals triggered by other stimuli will be discussed. Finally, a case study will illustrate how the many mechanisms are coordinated to moderate Ca2+-dependent activities in the cardiovascular system.